Pengaruh Teknik Assertive Training Terhadap Penyesuaian Diri Siswa di SMAS Darul Hikmah Mataram - M Syarafuddin; Yuliastri Yuliastri (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to determine the effect of assertive training techniques on the adaptation of class X students at SMAS Darul Hikmah Mataram. This research method uses experiments. The population in this study were all students of class X SMAS Darul Hikmah Mataram, amounting to 16 students. In this study using purposive sampling to determine the sample and produced 6 students to study who experienced low adjustment. Data collection techniques using questionnaires, observation, interviews, and documentation. Data analysis techniques using statistical analysis with the t-test formula. In accordance with the results of the calculation of tcount obtained from the results of the study showed 12,156. While the t-test value in the table with db (N-1) = 6-1 = 5 with a significance level of 0.05 or 5% = 2.015. So the results obtained in this study are greater than t table (12,156> 2,015), thus the conclusion obtained in this study is that there is an influence of assertive training techniques on the adjustment of class X students in SMAS Darul Hikmah Mataram.